The Role of Rooting Cofactors in Improvement of Rooting Response in Difficult-to-Root Cuttings of Nerium Oleander Var. White (Vs .Pink var.) - Abdullah I. Shaheed (Journal of Global Pharma Technology, 2019)
In the current study, it has been identified that white oleander is impossible or difficult-to-root (0.00%) while, pink oleander is slightly difficult -to-root cuttings (6.67 %) in absence of supplied auxin (treated with distilled water). However, to improve the capability of rooting response of white oleander cuttings (difficult-to-root variety), six treatments have been employed including identified (e.g. o-coumaric acid) and un-identified co-factors (e.g. whitetope seeds extract), individually and in combination with IBA and the results revealed the followings:-Some of these treatments were at high level of significance (P0.05), verifying an original  successful and economical acceptance by vegetative propagation of difficult-to-root cuttings (white oleander) that  caused (induced) to root and increased vegetative traits, when supplied individually or in combination with  IBA, the highest values are represented in the following treatments:-O-Coumaric acid  in combination with  IBA  was induced  rooting  percentage (33.33%), average roots no.(23.67), chlorophyll content (28.03 SPAD unit) and length of branches (15.00 cm)  Whitetope seeds extract in combination with IBA, induced rooting response (20%), roots no. (28.60)/cutting, leaves no. (39.30) and leaf surface area (15.80) cm2  IBA, Whitetope seeds extract, were induced rooting percentage (6.67%).   As a comparison with pink oleander, all treatments that have been tested were stimulated rooting  when supplied in combination  with   IBA , at a rate higher than white  oleander except d/H2O, o- Coumaric acid  and whitetope extract treatments, where the response is zero. However, the maximum response in rooting % was found with combination between IBA and o- Coumaric acid followed by IBA+whitetope extract (33.33%). However, the discussion was focused on a)phenolic compounds as auxin protectors from destruction by IAA-O enzyme  b) o-coumaric acid as anti-oxidant by activation of electronic conjugation c) plant extracts containing substances considered as precursor for its conversion into non enzymetic anti-oxidant such as GSH, proline. etc and its role in AsA-GSH cycle, or substances that enhances CAT, SOD enzymes that activates the anti-oxidant defense mechanisms and consequently enhances rooting response.Keywords:- Anti-oxidants, Co-factor, Difficult-to-root cuttings, IAA-O, IBA, Improvement of rooting response, Inhibitors, Nerium Oleandr, o-Coumaric acid and whitetope  seeds extract.